(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the frequency of intra operative anatomical variations in patients undergoing surgical release for de Quervain’s disease. Methods: We conducted this descriptive study in Department of Orthopaedics and spine surgery Khyber Girls Medical College/Hayatabad Medical Complex Peshawar from 21st January 2017 to 24th December 2019.All patients of de Quervain’s disease fulfilling the inclusion criteria were surgically released under local anaesthesia. The frequency of intra operative anatomical variations of Abductor Pollicis Longus(APL) and Extensor Pollicis Brevis(EPB) were noted and classified according to the Hiranuma classification. Results: We enrolled 80 patients (86 wrists) in our study. The mean age was 41years(range 25 to 75 years).Female patients were 71(88.7%) and male patients were only 9(11.2%).Majority(88.7%,n=71) of patients had right sided de Quervain’s disease while left sided was involved in 3(3.7%) patients and 6(7.5%) patients had bilateral de Quervain’s disease. Hiranuma Type II was the predominant anatomical variation noted in 53(61.6%) wrists followed by type I(26.7%,n=23).Majority(91.8%,n=79) of wrists had 1 APL tendon followed by 2 APL tendons in 4(4.6%) and 3 tendons in 3(3.4%) wrists. The number of EPB was 1 in 82(95.3%) wrists,2 in 1(1.1%) and absent EPB in 03(3.4%) wrists. Conclusion: Majority of our patients had APL and EPB in separate compartments with complete septation and had single APL and EPB tendon in each compartment. On the contrary the traditional or classical presentation of APL and EPB lying side by side in a single compartment was noted in less number of patients.